POLA KECENDERUNGAN MUHAMMAD NASHIRUDDIN AL-ALBANI DALAM MEMAHAMI HADIS - Muhid, Muhid; Muthoharoh, Isnaini Lu'lu' Atim; Nurita, Andris (Dar el-Ilmi : Jurnal Studi Keagamaan, Pendidikan dan Humaniora, 2023)
The scope of the mosque with all its problems is not a new thing which is the subject of discussion among the people. Including the issue of the Friday call to prayer with the facilities and infrastructure used to support the course of worship activities. Among the many scholars' who responded to this matter, there is the contemporary muhaddith Muhammad Nashiruddin al-Albani who specifically gave birth to a paper entitled al-Ajwibah an-Nafi'ah in the style of As'ilah Masjid al-Jami'ah. With good credibility and capability, al-Albani is not always silent from various accusations related to his inconsistency in presenting various arguments. Qualitative research based on literature and the application of the rules of al-Tamyi>z Bayna al-Wasilah al-Mutaghayyirah wa al-Hadf al-Tha>bit is expected to reveal in detail the pattern of al-Albani's tendency to understand a hadith. The results of this study indicate that al-Albani's tips and enthusiasm in grounding and voicing the sunnah sometimes tend to be textual in addressing a number of hadiths mainly related to mosque issues. So that this pattern of understanding gives birth to a number of conclusions that seem lateral and not in line with the pace of development of the times.